2002
DOI: 10.1152/ajplung.00206.2001
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase promotes NF-κB activation and proliferation in human airway smooth muscle

Abstract: Evidence is rapidly accumulating that low-activity-reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidases homologous to that in phagocytic cells generate reactive oxygen species as signaling intermediates in both endothelium and vascular smooth muscle. We therefore explored the possibility of such an oxidase regulating growth of airway smooth muscle (AWSM). Proliferation of human AWSM cells in culture was inhibited by the antioxidants catalase and N-acetylcysteine, and by the flavoprotein inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 64 publications
6
63
0
Order By: Relevance
“…The generation of ROS by NE appears to be mediated by different types of NADPH oxidases (77,78) and may also require PKC activation (74). This may mean that ROS act upstream of NF-κB in MUC5AC expression because ROS activation of NF-κB in airway epithelial and smooth muscle cells has been observed (79)(80)(81).…”
Section: Regulation Of Muc5ac Expression By Nuclear Factor-κbmentioning
confidence: 99%
“…The generation of ROS by NE appears to be mediated by different types of NADPH oxidases (77,78) and may also require PKC activation (74). This may mean that ROS act upstream of NF-κB in MUC5AC expression because ROS activation of NF-κB in airway epithelial and smooth muscle cells has been observed (79)(80)(81).…”
Section: Regulation Of Muc5ac Expression By Nuclear Factor-κbmentioning
confidence: 99%
“…Rac1 constitutes part of the NADPH oxidase complex that generates superoxide and H 2 O 2 (74,75). Intracellular H 2 O 2 is increased after mitogen treatment of rat tracheal myocytes (76), bovine tracheal myocytes (73), and human bronchial smooth muscle cells (77). Accordingly, treatment with antioxidants attenuates both mitogen-activated cyclin D1 expression and DNA synthesis in these cells (73,76,77).…”
Section: Biochemical Mechanisms Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…Intracellular H 2 O 2 is increased after mitogen treatment of rat tracheal myocytes (76), bovine tracheal myocytes (73), and human bronchial smooth muscle cells (77). Accordingly, treatment with antioxidants attenuates both mitogen-activated cyclin D1 expression and DNA synthesis in these cells (73,76,77). Finally, in bovine cells, Rac1 induces transactivation of the cyclin D1 promoter CREB/ATF2 binding site, which is attenuated by antioxidants (71).…”
Section: Biochemical Mechanisms Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…As an adaptation to acute exercise-induced oxidative stress, the increased level of ROS induces antioxidant enzyme gene expression via an intracellular signaling pathway, which involves the redox regulated transcription factor, NF-B (17). Furthermore, using p22phox knockout mice, it has been demonstrated that the NADPH oxidase system plays a critical role in NF-B activation (4). Therefore, the NADPH oxidase system is a potential mechanism through which exercise training may modulate systemic oxidative stress levels.…”
mentioning
confidence: 99%